Currículo inovador: a realidade de uma escola do Ensino Fundamental II - Soares, Cristine Rodrigues (2018)
The current educational scenario in Brazil took us to rethink about the educative practice, looking for strategies in order to improve the educational ways and results obtained by the learners. The desirable transformations to our country should be started at school, through resignificances of the teacher-student action in the educational process for the changes to take effect. This paper aims analyzing results from the implementation process of an innovational curriculum that has among its proposals develop a teaching methodology based on the pedagogy of Célestin Freinet, in order to enable the realization of a new learning conception, human relationships, organization of spaces and experiences by the students from a private middle school in São Paulo city. As a theoretical conceptual basis has innovational concepts of education and curriculum, this study initially considered, for analysis purposes, some school documents in which the mentioned project and the current legislation were implemented. The objective here is understand the educational context and the implementation way of developed proposal. Based on a qualitative approach, this field research was chosen in order to characterize the teachers’ perceptions in the educational process experienced at the middle school during the period that covered the implementation and consolidation of the project from 2012 to 2017. The instruments used to collect data were structured interviews with all professionals who have acted directly in this project and some data based on observation records of the everyday school. The results allow to prove that the innovative curriculum is able to increase professionals interest and motivation. In addition, there were also significant skills and competences that allow them to improve their academic performance and human formation. Through this research, it was also possible to validate the condition that innovating in education needs comprehension and commitment of teaching staff and all involved community